Oxide-coated fibrous silicon-carbon composite material and preparation method thereof

By covering amorphous carbon on the surface of metal nanowires and chemically depositing lithium salts to form oxide-covered fibrous silicon-carbon composites, the problems of low rate performance and high expansion performance of existing silicon-carbon composites are solved, and higher rate performance and lower expansion performance are achieved.

CN119864397AActive Publication Date: 2025-04-22SICHUAN KUNTIAN NEW ENERGY TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510057261.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-22
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

The existing silicon-carbon composite materials have low rate performance and high expansion performance, which limits the cycle life and charge and discharge efficiency of lithium-ion batteries.

Method used

The fibrous silicon-carbon composite material is coated with oxides. By coating amorphous carbon on the surface of metal nanowires and chemically depositing lithium salts in their porous carbons, forming a core-shell structure to enhance electron conductivity and reduce expansion.

Benefits of technology

It improves the rate performance of silicon-carbon composite materials, reduces expansion performance, extends the cycle life of lithium-ion batteries and improves the charging and discharging efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864397A_ABST
    Figure CN119864397A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of material preparation, and provides an oxide-coated fibrous silicon-carbon composite material and a preparation method thereof. The oxide-coated fibrous silicon-carbon composite material is of a core-shell structure and sequentially comprises an inner core, a first shell and a second shell from inside to outside, the inner core is made of a metal-doped silicon-carbon material, the first shell is made of metal oxide, the second shell is made of amorphous carbon, and the mass ratio of the inner core to the first shell to the second shell is (80-90): (5-10): (5-10). According to the technical scheme, the problems of low rate capability and high expansion performance of the silicon-carbon composite material in the related technology are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of material preparation, and in particular to an oxide-coated fibrous silicon-carbon composite material and a preparation method thereof. Background Art

[0002] Silicon-carbon composite materials are very promising negative electrode materials for lithium-ion batteries. Due to their high specific capacity and good cycle stability, they can effectively improve the energy density of batteries and extend the service life of batteries. They have broad application prospects in high-performance electric vehicle batteries, portable electronic device batteries, etc. At present, the silicon-carbon composite materials on the market are mainly prepared by depositing nanosilicon in porous carbon by silane cracking method and passivating its surface. The morphology of the material is a granular structure, which causes its full-charge expansion to be high; and due to the porous structure of the inner core, the material has many defects and poor ion conductivity. This will not only reduce the charge and discharge efficiency of the battery and affect the rate performance of the battery, but also limit the cycle life of the battery. Therefore, it is necessary to develop a silicon-carbon composite material with high rate performance and low expansion. Summary of the invention

[0003] The present invention provides an oxide-coated fibrous silicon-carbon composite material and a preparation method thereof, which solves the problems of low rate performance and high expansion performance of the silicon-carbon composite material in the related art.

[0004] The technical solution of the present invention is as follows: The present invention proposes an oxide-coated fibrous silicon-carbon composite material, wherein the composite material is a core-shell structure, which comprises, from the inside to the outside, an inner core, a first outer shell and a second outer shell, wherein the inner core is a metal-doped silicon-carbon material, the first outer shell is a metal oxide, and the second outer shell is amorphous carbon, and the mass ratio of the inner core, the first outer shell and the second outer shell is 80~90:5~10:5~10.

[0005] As a further technical solution, the inner core comprises the following component raw materials in parts by weight: 100 parts of polymer, 40-50 parts of metal wire, 1-5 parts of dispersant, 100-500 parts of carbon-based compound, and 1-5 parts of lithium compound.

[0006] As a further technical solution, the carbon-based compound includes one or more of glucose, sucrose, and maltose.

[0007] As a further technical solution, the method for preparing the inner core comprises the following steps: S1. The polymer is dispersed in water, and a dispersant and a metal wire are added in sequence to obtain a metal wire solution; S2, dispersing the carbon-based compound in water, adding the metal wire solution and the lithium compound in sequence, filtering, carbonizing and activating after the reaction, to obtain fibrous metal-doped porous carbon; S3. After depositing nano-silicon on fibrous metal-doped porous carbon, a core is obtained.

[0008] As a further technical solution, the metal wire is a metal nanowire.

[0009] In the present invention, amorphous carbon is coated on the surface of metal nanowires, carbonized, and the fibrous structure of the metal nanowires is used as a matrix to coat porous carbon on its surface, thereby improving the electronic conductivity of the material, and the fibrous structure has lower expansion than the granular structure. At the same time, lithium salt is chemically deposited in the porous carbon, activated, and lithium-doped fibrous metal-doped porous carbon is obtained, which reduces defects, improves the initial efficiency and reduces expansion.

[0010] As a further technical solution, the mass ratio of the polymer to water is 1~5:100.

[0011] As a further technical solution, the mass ratio of the polymer, dispersant and metal wire is 100:1:40~100:5:50.

[0012] As a further technical solution, the mass ratio of the porous carbon to the water is 1-10:100.

[0013] As a further technical solution, the mass ratio of the porous carbon to the metal wire solution is 100:100-500.

[0014] As a further technical solution, the reaction temperature is 50-100° C., and the reaction time is 1-6 hours.

[0015] As a further technical solution, the gas introduced during the carbonization is carbon dioxide, the flow rate is 10 SCCM, and the introduction time is 60 minutes.

[0016] As a further technical solution, the carbonization temperature is 700-1000° C., and the carbonization time is 1-6 hours.

[0017] As a further technical solution, the activation temperature is 1200~1500°C.

[0018] As a further technical solution, the deposition method is chemical deposition.

[0019] As a further technical solution, the deposition temperature is 450-550° C., and the gas used for the deposition is a silane mixed gas, which is composed of silane gas and nitrogen in a volume ratio of 1-5:10.

[0020] As a further technical solution, the silane mixed gas is introduced at a flow rate of 10-50 SCCM for a time of 30-300 min.

[0021] As a further technical solution, after the fibrous metal-doped porous carbon deposits nano-silicon, the following steps are also included: cooling to room temperature, introducing oxygen mixed gas, and obtaining a core.

[0022] As a further technical solution, the oxygen mixed gas consists of oxygen and nitrogen in a volume ratio of 1 to 5:10.

[0023] As a further technical solution, the oxygen mixed gas is introduced for a time of 10 to 60 minutes.

[0024] As a further technical solution, the polymer includes one or more of polyacrylic acid, polyvinyl pyrrolidone, and polyacrylamide.

[0025] As a further technical solution, the metal wire includes one or more of nano-silver wire, nano-copper wire, nano-nickel wire, and nano-magnesium wire.

[0026] As a further technical solution, the length of the metal wire is 0.5-2 μm and the diameter is 10-500 nm.

[0027] As a further technical solution, the lithium compound includes one or more of lithium difluorooxalate, lithium difluorophosphate, lithium tetrafluoroborate, lithium difluoroborate, and lithium trifluoromethanesulfonate.

[0028] As a further technical solution, the dispersant includes one or more of polypropylene alcohol, polyvinyl acetate, and polyacrylate.

[0029] As a further technical solution, when the dispersant is polyacrylate, the polyacrylate is composed of polymethyl acrylate and poly(2,2,2-trifluoroethyl acrylate) in a mass ratio of 1:2-3.

[0030] In the present invention, polymethyl acrylate and poly (2,2,2-trifluoroethyl acrylate) are used as dispersants at the same time, and the synergistic effect of the two is exerted to further improve the rate performance of the composite material and reduce the expansion performance of the silicon-carbon composite material.

[0031] The present invention also provides a method for preparing an oxide-coated fibrous silicon-carbon composite material, comprising the following steps: depositing metal oxide and amorphous carbon on the surface of an inner core in sequence to obtain a composite material.

[0032] As a further technical solution, the deposition of metal oxide includes the following steps: placing the inner core in a vacuum reaction device, introducing metal oxide gas in a reducing gas atmosphere for atomic vapor deposition, so as to obtain a metal oxide-coated inner core.

[0033] As a further technical solution, the vacuum degree is ≤1 Torr.

[0034] As a further technical solution, the reducing gas atmosphere includes one or both of hydrogen and carbon monoxide.

[0035] As a further technical solution, the deposition temperature is 500-1100° C., and the deposition time is 10-60 min.

[0036] As a further technical solution, the flow rate of the introduced metal oxide gas is 10-100 SCCM.

[0037] As a further technical solution, the deposition of amorphous carbon includes the following steps: transferring the metal oxide coated core to a tube furnace, introducing carbon-containing gas to perform atomic vapor deposition, and obtaining a composite material.

[0038] As a further technical solution, the deposition temperature is 700-900° C., and the deposition time is 30-300 min.

[0039] As a further technical solution, the carbon-containing gas is acetylene carbon source gas.

[0040] As a further technical solution, the flow rate of the carbon-containing gas is 10-50 SCCM.

[0041] As a further technical solution, the metal oxide includes one or more of lithium oxide, magnesium oxide, and nickel oxide.

[0042] The working principle and beneficial effects of the present invention are: In the present invention, a metal-doped silicon-carbon material is used as the core, and metal oxide is deposited on its surface to form a continuous conductive network on the surface of the core, providing a channel for rapid transmission of electrons, and amorphous carbon is deposited again on its outer surface to reduce direct contact with the electrolyte, reduce side reactions, and improve the initial efficiency, thereby improving the rate performance of the silicon-carbon composite material and reducing the expansion performance of the silicon-carbon composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0044] Figure 1 This is a SEM image of the oxide-coated fibrous silicon-carbon composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0045] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] In the following examples and comparative examples: Polyacrylic acid: effective content is 50wt%, the manufacturer is Zibo Dongrun Chemical Technology Co., Ltd.; Polymethyl acrylate: weight average molecular weight is 40000, purchased from Shanghai Jizhi Biochemical Technology Co., Ltd.; Silver nanowire: 1 μm in length and 120 nm in diameter; Nano magnesium wire: 1 μm in length and 120 nm in diameter; Nano copper wire: 1 μm in length and 120 nm in diameter; Silver particles: average particle size is 40nm; Polyvinyl pyrrolidone: average molecular weight 8000, purchased from MacLean Reagent; Polyacrylamide: non-ionic, molecular weight 12 million, purchased from MacLean Reagent; Polypropylene alcohol: number average molecular weight 3000, purchased from MacLean reagent; Polyvinyl acetate: weight average molecular weight is 10000, purchased from MacLean Reagent.

[0047] Example 1 The preparation method of the kernel comprises the following steps: S1, dispersing 100 parts of polyacrylic acid in 5000 parts of water, adding 1 part of polymethyl acrylate and 40 parts of nano silver wires in sequence, and dispersing them evenly to obtain a metal wire solution; S2, 100 parts of glucose were dispersed in 1000 parts of water, 100 parts of metal wire solution were added and mixed evenly, and then 1 part of lithium difluorooxalate was added, and the reaction was carried out at a temperature of 50°C for 6 hours by chemical deposition method, filtered, and the obtained material was carbonized at 700°C for 6 hours, and then the temperature was raised to 1200°C, carbon dioxide gas was introduced, and activated at a flow rate of 50SCCM for 60 minutes to obtain fibrous metal-doped porous carbon; S3, 100g of fibrous metal-doped porous carbon was transferred to a fluidized bed, nitrogen gas was introduced to exhaust the air in the tube, and then the mixture was heated to 450°C and silane mixed gas (volume ratio of disilane gas: nitrogen = 1:10) was introduced at a flow rate of 10SCCM for 300min, and then the mixture was cooled to room temperature and oxygen mixed gas (volume ratio of oxygen: nitrogen = 1:10) was introduced for 60min to obtain a core; S4. The inner core is transferred to a vacuum furnace, and then the silicon-carbon precursor material is placed in a vacuum reaction device through atomic vapor deposition with a vacuum degree of 0.1 Torr. In a hydrogen atmosphere, the temperature is raised to 500°C, and lithium oxide gas is introduced while maintaining a hydrogen flow rate of 10 SCCM. The deposition is performed for 60 minutes to obtain a first outer shell. The obtained material is then transferred to a tubular furnace, and nitrogen is introduced to exhaust the air in the tube. The temperature is then raised to 700°C, and acetylene carbon source gas is introduced at a flow rate of 10 SCCM for 300 minutes to obtain a second outer shell, thereby obtaining a composite material, wherein the mass ratio of the inner core, the first outer shell, and the second outer shell is 80:5:5.

[0048] The SEM image of the oxide-coated fibrous silicon-carbon composite material prepared in Example 1 is as follows: Figure 1 shown.

[0049] Example 2 The preparation method of the kernel comprises the following steps: S1, dispersing 100 parts of polyvinyl pyrrolidone in 7500 parts of water, and sequentially adding 3 parts of polyvinyl acetate and 45 parts of nano magnesium wires, dispersing them evenly, to obtain a metal wire solution; S2, 100 parts of glucose were dispersed in 5000 parts of water, 300 parts of metal wire solution were added and mixed evenly, and then 3 parts of lithium difluorophosphate were added, and the reaction was carried out at a temperature of 80°C for 3 hours by chemical deposition method, filtered, and the obtained material was carbonized at 900°C for 3 hours, and then the temperature was raised to 1350°C, carbon dioxide gas was introduced, and activated for 60 minutes at a flow rate of 50SCCM to obtain fibrous metal-doped porous carbon; S3, transferring the fibrous metal-doped porous carbon to a fluidized bed, introducing nitrogen gas to exhaust the air in the tube, then heating to 500°C, introducing a silane mixed gas (volume ratio of disilane gas: nitrogen = 3:10) at a flow rate of 20 SCCM for 200 min, then cooling to room temperature, and introducing an oxygen mixed gas (volume ratio of oxygen: nitrogen = 3:10) for 30 min to obtain a core; S4. The inner core is transferred to a vacuum furnace, and then the silicon-carbon precursor material is placed in a vacuum reaction device through atomic vapor deposition. The vacuum degree is 0.1 Torr. In a hydrogen atmosphere, the temperature is raised to 850°C, and magnesium oxide gas is introduced while maintaining a hydrogen flow rate of 50 SCCM. The deposition is performed for 30 minutes to obtain a first shell. The obtained material is then transferred to a tubular furnace, and nitrogen is introduced to exhaust the air in the tube. The temperature is then raised to 800°C, and acetylene carbon source gas is introduced at a flow rate of 30 SCCM for 200 minutes to obtain a second shell, thereby obtaining a composite material, wherein the mass ratio of the inner core, the first shell, and the second shell is 90:8:8.

[0050] Example 3 The preparation method of the kernel comprises the following steps: S1, dispersing 100 parts of polyacrylamide in 10,000 parts of water, adding 5 parts of polypropylene alcohol and 50 parts of nano copper wires in sequence, dispersing evenly, to obtain a metal wire solution; S2, 100 parts of glucose were dispersed in 10000 parts of water, 500 parts of metal wire solution were added and mixed evenly, and then 5 parts of lithium tetrafluoroborate were added, and the reaction was carried out at a temperature of 100°C for 1 hour by chemical deposition method, filtered, and the obtained material was carbonized at 1000°C for 1 hour, and then the temperature was raised to 1500°C, carbon dioxide gas was introduced, and activated at a flow rate of 50SCCM for 60 minutes to obtain fibrous metal-doped porous carbon; S3, transferring the fibrous metal-doped porous carbon to a fluidized bed, introducing nitrogen gas to exhaust the air in the tube, then heating to 500°C, introducing a silane mixed gas (volume ratio of disilane gas: nitrogen = 5:10) at a flow rate of 50 SCCM for 30 minutes, then cooling to room temperature, and introducing an oxygen mixed gas (volume ratio of oxygen: nitrogen = 5:10) for 10 minutes to obtain a core; S4. The inner core is transferred to a vacuum furnace, and then the silicon-carbon precursor material is placed in a vacuum reaction device through atomic vapor deposition. The vacuum degree is 0.1 Torr. In a hydrogen atmosphere, the temperature is raised to 1100°C, and nickel oxide gas is introduced while maintaining a hydrogen flow rate of 100 SCCM. Deposition is performed for 10 minutes to obtain a first shell. The resulting material is then transferred to a tubular furnace, and nitrogen is introduced to exhaust the air in the tube. The temperature is then raised to 900°C, and acetylene carbon source gas is introduced for 30 minutes at a flow rate of 50 SCCM to obtain a second shell, thereby obtaining a composite material, wherein the mass ratio of the inner core, the first shell, and the second shell is 100:10:10.

[0051] Example 4 Compared with Example 1, Example 4 is different in that, in the preparation of the inner core, the lithium difluorooxalate in S2 is added together with the polymethyl acrylate in S1 into the aqueous solution of polyacrylic acid to obtain a metal wire solution.

[0052] Example 5 Compared with Example 1, Example 5 is different in that lithium difluorooxalate is not added.

[0053] Example 6 Compared with Example 1, Example 6 is different in that the nano silver wires are replaced with an equal amount of silver particles.

[0054] Example 7 Compared with Example 1, Example 7 is different in that polymethyl acrylate is replaced with polymethyl acrylate and poly(2,2,2-trifluoroethyl acrylate) in a mass ratio of 1:2.

[0055] Example 8 Compared with Example 1, Example 8 is different in that polymethyl acrylate is replaced with polymethyl acrylate and poly(2,2,2-trifluoroethyl acrylate) in a mass ratio of 1:3.

[0056] Comparative Example 1 Compared with Example 1, the difference of Comparative Example 1 is that, in this embodiment, step S4 is: S4. The inner core is transferred to a vacuum furnace, and then to a tubular furnace. Nitrogen is introduced to exhaust the air in the tube, and then the temperature is raised to 700°C, and acetylene carbon source gas is introduced at a flow rate of 10 SCCM for 300 minutes to obtain a first outer shell; then the inner core is transferred to a vacuum furnace, and then the silicon-carbon precursor material is placed in a vacuum reaction device by atomic vapor deposition with a vacuum degree of ≤1 Torr. In a hydrogen atmosphere, the temperature is raised to 500°C, and lithium oxide gas is introduced while maintaining a hydrogen flow rate of 10 SCCM. The gas is deposited for 60 minutes to obtain a second outer shell, i.e., a composite material is obtained, wherein the mass ratio of the inner core, the first outer shell, and the second outer shell is 80:5:5.

[0057] Comparative Example 2 Compared with Example 1, the difference of Comparative Example 2 is that, in this embodiment, step S4 is: S4. The inner core is transferred to a vacuum furnace, and then to a tubular furnace. Nitrogen is introduced to exhaust the air in the tube, and then the temperature is raised to 700°C, and acetylene carbon source gas is introduced at a flow rate of 10 SCCM for 300 minutes to obtain the outer shell; a composite material is obtained, in which the mass ratio of the inner core to the outer shell is 80:10.

[0058] Comparative Example 3 Compared with Example 1, the difference of Comparative Example 3 is that, in this embodiment, step S4 is: S4. The inner core is transferred to a vacuum furnace, and then the silicon-carbon precursor material is placed in a vacuum reaction device through atomic vapor deposition. The vacuum degree is ≤1 Torr. In a hydrogen atmosphere, the temperature is raised to 500°C, and lithium oxide gas is introduced while maintaining a hydrogen flow rate of 10 SCCM. The deposition is performed for 60 minutes to obtain an outer shell, thereby obtaining a composite material, wherein the mass ratio of the inner core to the outer shell is 80:10.

[0059] Comparative Example 4 Compared with Example 1, the difference of Comparative Example 4 is that step S1 in this embodiment is: dispersing 100 parts of polyacrylic acid in 5000 parts of water, adding 1 part of polyacrylate and 40 parts of nano silver wires in sequence, dispersing them evenly, and obtaining a metal wire solution.

[0060] Comparative Example 5 Compared with Example 1, the difference of Comparative Example 5 is that the composite material in this comparative example is the core prepared in Example 1.

[0061] The silicon-carbon composite materials obtained in Examples 1 to 8 and Comparative Examples 1 to 5 were tested according to the following method: 1. SEM test: The oxide-coated fibrous silicon-carbon composite material prepared in Example 1 was subjected to SEM test. The results are as follows: Figure 1 As shown by Figure 1 It can be seen that the material presents a fibrous structure with a length ranging from 1 to 10 μm and a diameter ranging from 10 to 100 nm.

[0062] 2. Physical and chemical tests: According to the test method specified in GB / T 38823-2020 "Silicon Carbon", the tap density and specific surface area of ​​the composite materials in Examples 1 to 8 and Comparative Examples 1 to 5 were tested, and the powder resistivity of the powder materials was tested by a four-probe tester. The test results are shown in Table 1 below.

[0063] 3. Button cell test: The silicon-carbon composite materials prepared in Examples 1 to 8 and Comparative Examples 1 to 5 were assembled into button cells according to the following method: The silicon-carbon composite material was used as the negative electrode, and was assembled into a button cell with a lithium sheet, an electrolyte and a diaphragm in a glove box with argon and water content less than 0.1 ppm. The diaphragm was celegard 2400; the electrolyte was a solution of LiPF6, in which the concentration of LiPF6 was 1 mol / L, and the solvent was a mixed solution of ethylene carbonate and diethyl carbonate in a weight ratio of 1:1.

[0064] The button cells were marked as A-1, B-1, C-1, D-1, E-1, F-1, G-1, H-1, I-1, G-1, K-1, L-1, and M-1, respectively. The performance of the button cells was then tested using a blue battery tester. The test conditions were: 0.1C rate charge and discharge, a voltage range of 0.005-2V, and the cycle was stopped after 3 weeks. The discharge capacity under 1C was then tested, and the 1C / 0.1C rate performance and cycle performance (25±3°C, 0.1C / 0.1C, 100 weeks) were calculated. At the same time, the button cells were fully charged to 100% SOC, and the full-charge expansion of the negative electrode sheet was tested. The test results are shown in Table 2 below.

[0065] 4. Soft pack battery performance test: The silicon-carbon composite materials prepared in Examples 1 to 8 and Comparative Examples 1 to 5 were doped with 95% artificial graphite as the negative electrode active material and mixed with the positive electrode active material ternary material (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3O2), electrolyte and diaphragm are assembled into 5Ah soft-pack batteries, wherein the diaphragm is celegard 2400, the electrolyte is LiPF6 solution (the solvent is a mixed solution of EC, DEC, and EMC with a volume ratio of 1:1:1, and the concentration of LiPF6 is 1.1 mol / L), and the prepared soft-pack batteries are marked as A-2, B-2, C-2, D-2, E-2, F-2, G-2, H-2, I-2, G-2, K-2, L-2, and M-2, and the cycle and rate performance of the batteries are tested. Cycle performance: the cycle performance of the battery is tested at a charge and discharge rate of 1C / 1C, 500 cycles, a voltage range of 2.5V~4.2V, and a temperature of 25±3℃; rate performance: the capacity of the battery is tested at 0.33C, 0.5C, 1C, and 2C, respectively, and then the rate performance at different rates is calculated. The test results are shown in Table 3 below.

[0066] The test results are shown in the following table: Table 1 Performance test results of silicon-carbon composite materials obtained in Examples 1 to 8 and Comparative Examples 1 to 5

[0067] Table 2 Performance test results of silicon-carbon composite materials obtained in Examples 1 to 8 and Comparative Examples 1 to 5

[0068] Table 3 Performance test results of silicon-carbon composite materials obtained in Examples 1 to 8 and Comparative Examples 1 to 5

[0069] Compared with Comparative Examples 1 to 3 and 5, Example 1 uses a metal-doped silicon-carbon material as the core, and is sequentially coated with a first shell and a second shell. As a result, the physical and chemical properties, button battery performance, and soft-pack battery performance of Example 1 are all better than those of Comparative Examples 1 to 3 and 5, indicating that when a metal-doped silicon-carbon material is used as the core, a metal oxide is used as the first shell, and amorphous carbon is used as the second card layer, the electrochemical properties of the composite material can be improved.

[0070] Compared with Example 1, in Example 4, lithium difluorooxalate was added to the aqueous solution of polyacrylic acid together with the polymethyl acrylate in S1 to obtain a metal wire solution. In Example 5, lithium difluorooxalate was not added. As a result, the physical and chemical properties, button cell performance and soft-pack cell performance of Example 1 were better than those of Examples 4 and 5, indicating that when the polymers are mixed first and then lithium difluorooxalate is added, the electrochemical properties of the composite material can be further improved.

[0071] Compared with Example 6 and Comparative Example 4, Example 1 adds nanometal wires. As a result, the physical and chemical properties, button battery performance and soft-pack battery performance of Example 1 are better than those of Example 6 and Comparative Example 4, indicating that when the added metal is nanometal wires, the electrochemical properties of the obtained composite material are better.

[0072] Compared with Example 1, Examples 7 and 8 simultaneously added polymethyl acrylate and poly (2,2,2-trifluoroethyl acrylate) as dispersants. As a result, the physical and chemical properties, button cell performance and soft-pack cell performance of Examples 7 and 8 were better than those of Example 1, indicating that polymethyl acrylate and poly (2,2,2-trifluoroethyl acrylate) play a synergistic role and can further improve the electrochemical properties of the composite material.

[0073] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An oxide-coated fibrous silicon-carbon composite material, characterized in that: The composite material is a core-shell structure, which comprises a core, a first shell and a second shell from the inside to the outside. The core is a metal-doped silicon-carbon material, the first shell is a metal oxide, and the second shell is amorphous carbon. The mass ratio of the core, the first shell and the second shell is 80~90:5~10:5~10.

2. The oxide-coated fibrous silicon-carbon composite material according to claim 1, characterized in that: The inner core comprises the following raw materials in parts by weight: 100 parts of polymer, 40-50 parts of metal wire, 1-5 parts of dispersant, 100-500 parts of carbon-based compound and 1-5 parts of lithium compound.

3. The oxide-coated fibrous silicon-carbon composite material according to claim 1, characterized in that: The preparation method of the core comprises the following steps: S1. The polymer is dispersed in water, and a dispersant and a metal wire are added in sequence to obtain a metal wire solution; S2, dispersing the carbon-based compound in water, adding the metal wire solution and the lithium compound in sequence, filtering, carbonizing and activating after the reaction, to obtain fibrous metal-doped porous carbon; S3. After depositing nano-silicon on fibrous metal-doped porous carbon, a core is obtained.

4. The oxide-coated fibrous silicon-carbon composite material according to claim 2, characterized in that: The polymer includes one or more of polyacrylic acid, polyvinyl pyrrolidone and polyacrylamide.

5. The oxide-coated fibrous silicon-carbon composite material according to claim 2, characterized in that: The metal wires include one or more of nano-silver wires, nano-copper wires, nano-nickel wires, and nano-magnesium wires.

6. The oxide-coated fibrous silicon-carbon composite material according to claim 2, characterized in that: The lithium compound includes one or more of lithium difluorooxalate, lithium difluorophosphate, lithium tetrafluoroborate, lithium difluoroborate, and lithium trifluoromethanesulfonate.

7. The oxide-coated fibrous silicon-carbon composite material according to claim 2, characterized in that: The dispersant includes one or more of polypropylene alcohol, polyvinyl acetate, and polyacrylate.

8. The oxide-coated fibrous silicon-carbon composite material according to claim 7, characterized in that: When the dispersant is polyacrylate, the polyacrylate is composed of polymethyl acrylate and poly(2,2,2-trifluoroethyl acrylate) in a mass ratio of 1:2-3.

9. The method for preparing an oxide-coated fibrous silicon-carbon composite material according to any one of claims 1 to 8, characterized in that: The following steps are involved: After metal oxide and amorphous carbon are sequentially deposited on the surface of the inner core, a composite material is obtained.

10. The method for preparing an oxide-coated fibrous silicon-carbon composite material according to claim 9, characterized in that: The metal oxide includes one or more of lithium oxide, magnesium oxide and nickel oxide.

Citation Information

Patent Citations

  • Silicon-based negative electrode material, preparation method thereof and related product

    CN112164780A

  • Method for preparing modified silicon-carbon composite material and modified silicon-carbon composite material

    CN115799492A

  • Preparation method and application of silicon-carbon composite material

    CN119029167A

  • Anode active material for lithium secondary battery comprising silicon nanoparticles and method for manufacturing the same

    KR1020180086000A

  • Core-shell high capacity nanowires for battery electrodes

    US20100330421A1